2020
DOI: 10.3390/ijms21165850
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Factors throughout Fetal Neurodevelopment: The Serotonin Link

Abstract: Serotonin (5-HT) is a critical player in brain development and neuropsychiatric disorders. Fetal 5-HT levels can be influenced by several gestational factors, such as maternal genotype, diet, stress, medication, and immune activation. In this review, addressing both human and animal studies, we discuss how these gestational factors affect placental and fetal brain 5-HT levels, leading to changes in brain structure and function and behavior. We conclude that gestational factors are able to interact and thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 305 publications
0
34
0
Order By: Relevance
“…This may be result of the influence of various fetal and/or maternal factors that were not controlled for in the present study. Indeed, fetal sex [34] and genotype [52] were reported to influence 5-HT uptake in rat and human placentas, respectively; others and we have found that maternal obesity and glucose tolerance in pregnancy modulate 5-HT system in the human placenta [17, 43, 53, 54], and various other gestational factors, such as maternal genotype, diet, stress, and immune activation, have been shown to influence fetal and placental 5-HT homeostasis [22]. However, it was outside the scope of the present study to understand regulatory influences and factors of the various 5-HT uptake systems in placenta and platelets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be result of the influence of various fetal and/or maternal factors that were not controlled for in the present study. Indeed, fetal sex [34] and genotype [52] were reported to influence 5-HT uptake in rat and human placentas, respectively; others and we have found that maternal obesity and glucose tolerance in pregnancy modulate 5-HT system in the human placenta [17, 43, 53, 54], and various other gestational factors, such as maternal genotype, diet, stress, and immune activation, have been shown to influence fetal and placental 5-HT homeostasis [22]. However, it was outside the scope of the present study to understand regulatory influences and factors of the various 5-HT uptake systems in placenta and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fetal sex 34 and genotype 58 were reported to influence 5-HT uptake in the plasma membrane vesicles isolated from rat and human placentas, respectively. Various other gestational factors such as maternal obesity and glucose tolerance 17,36,59,60 as well as maternal genotype, diet, stress and immune activation 22 have been also reported to influence placental or fetal 5-HT homeostasis. Understanding the regulatory influences of various factors on the 5-HT uptake systems in placenta and platelets, which was beyond the scope of the present study, warrants further investigation in studies employing full kinetic measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular targets underlining the long-lasting cognitive and behavioural outcomes of ethanol exposure include components of serotoninergic, GABAergic, glutamatergic and dopaminergic systems. Data from human and animal studies indicate that ethanol exposure during early brain development is able to block NMDA receptors, to exacerbate GABA A receptor action, to decrease 5-HT-binding and to decrease dopamine levels [8][9][10][11] .…”
mentioning
confidence: 99%